2017
DOI: 10.1007/s12040-017-0888-x
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based bivariate statistical techniques for groundwater potential analysis (an example of Iran)

Abstract: Groundwater potential analysis prepares better comprehension of hydrological settings of different regions. This study shows the potency of two GIS-based data driven bivariate techniques namely statistical index (SI) and Dempster-Shafer theory (DST) to analyze groundwater potential in Broujerd region of Iran. The research was done using 11 groundwater conditioning factors and 496 spring positions. Based on the ground water potential maps (GPMs) of SI and DST methods, 24.22% and 23.74% of the study area is cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Evidently, wells, springs, rivers, etc. are the point of discharge for groundwater from the aquifer layer [2,17]; hence, in this study, spring locations are identified as the groundwater resource indicators. An inventory map from comprehensive field surveys by the Iranian Department of Water Resource Management, Iran (Figure 1), pinpoints the locations of 917 springs.…”
Section: Study Area and Data Usedmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidently, wells, springs, rivers, etc. are the point of discharge for groundwater from the aquifer layer [2,17]; hence, in this study, spring locations are identified as the groundwater resource indicators. An inventory map from comprehensive field surveys by the Iranian Department of Water Resource Management, Iran (Figure 1), pinpoints the locations of 917 springs.…”
Section: Study Area and Data Usedmentioning
confidence: 99%
“…Groundwater is more reliable in terms of quality and availability since it exists in many geological formations and is naturally protected from direct contamination [12][13][14]. Moreover, according to the authors of [15][16][17], safe and sustainable water supply is only guaranteed through adequate groundwater resource assessment and planning. Haghizadeh et al [17] adds that proper GPM requires reliable information concerning procedures and associated conditioning factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In present the decades, groundwater recharge level has fallen due to unnecessary use and unscientific management plans [9]. Hence, aquifer potential determination through groundwater potentiality analysis is a good strategy in this field [10,11]. Different methods and models, techniques and processes were induced and used for the groundwater potentiality map (GWPM) or identification of areas having good potentiality of groundwater recharge.…”
Section: Introductionmentioning
confidence: 99%